Left vocal cord paralysis due to lymphadenopathy of mediastinal tuberculosis - Dikici, O¤uzhan; Bayar Muluk, Nuray (ENT Updates, 2013)
Though there are a lot of causes of vocal cord paralysis, such as trauma, cancer and surgery; idiopathic cases are also found. Vocal cord paralysis can be also seen in cases of mediastinal mass or tuberculosis which cause mediastinal lymphadenopathy. In this paper, a patient complaining of hoarseness with the diagnosis of left vocal cord paralysis was presented. Thoracic computed spiral tomography showed conglomerated mediastinal lymphadenopathy and biopsy was reported as granulomatous inflammation. Antituberculostatic therapy was administered to the patient and his follow-up procedures are continuing currently.